2017
DOI: 10.1515/znb-2017-0123
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of the germanides RE 3Pt4Ge6 (RE=Y, Pr, Nd, Sm, Gd–Dy)

Abstract: The germanides RE3Pt4Ge6 (RE=Y, Pr, Nd, Sm, Gd–Dy) have been synthesized by arc-melting of the elements followed by inductive annealing to improve the crystallinity and allow for structural order. The compounds have been studied by powder X-ray diffraction; additionally the structure of Y3Pt4Ge6 has been refined from single-crystal X-ray diffractometer data. It exhibits a (3+1)D modulated structure, indicating isotypism with Ce3Pt4Ge6. The crystal structure can be described as an intergrowth between YIrGe2- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In comparison with other intermetallic compounds, e.g. SmPdGa 3 (Δ E = 1346 K) or HP‐SmPdSn (Δ E = 1366 K) exhibit higher values, however, also a number of compounds with significantly lower energy values [Δ E = 265 K for SmRu 2 Zn 20 , 412 K for SmCo 2 Zn 20 , 454 K for Sm 3 Pt 4 Ge 6 , 480 K for Sm 2 RuAl 3 , 703 K for Sm 2 Rh 3 Sn 5 , 714 K for Sm 2 CoIn 8 , 850 K for SmOs 4 Sb 12 or finally 942(2) K for SmPt 6 Al 3 ] have been observed and reported. The ZFC/FC curves for Sm 2 Pt 6 Ga 15 are finally depicted in Figure (bottom), exhibiting a splitting of the ZFC and FC curves, underlining the ferrimagnetic ground state, in analogy to Pr 2 Pt 6 Ga 15 and Nd 2 Pt 6 Ga 15 described before.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with other intermetallic compounds, e.g. SmPdGa 3 (Δ E = 1346 K) or HP‐SmPdSn (Δ E = 1366 K) exhibit higher values, however, also a number of compounds with significantly lower energy values [Δ E = 265 K for SmRu 2 Zn 20 , 412 K for SmCo 2 Zn 20 , 454 K for Sm 3 Pt 4 Ge 6 , 480 K for Sm 2 RuAl 3 , 703 K for Sm 2 Rh 3 Sn 5 , 714 K for Sm 2 CoIn 8 , 850 K for SmOs 4 Sb 12 or finally 942(2) K for SmPt 6 Al 3 ] have been observed and reported. The ZFC/FC curves for Sm 2 Pt 6 Ga 15 are finally depicted in Figure (bottom), exhibiting a splitting of the ZFC and FC curves, underlining the ferrimagnetic ground state, in analogy to Pr 2 Pt 6 Ga 15 and Nd 2 Pt 6 Ga 15 described before.…”
Section: Resultsmentioning
confidence: 99%
“…The effective magnetic moment is slightly smaller than the value of 0.845 μ B of the free ion, δ = 247(2) K corresponds to ΔE = 706 K. The energy difference is smaller compared to the value of 1550 K predicted by Stewart, however, a look into the literature reveals that several compounds were shown to exhibit lower values. ΔE = 454 K are found for Sm 3 Pt 4 Ge 6 [66], 850 K for SmOs 4 Sb 12 [67], 1080 K for SmRh 4 B 4 [64], 412, 265, and 1488 K for SmCo 2 Zn 20 , SmRu 2 Zn 20 , and SmPd 2 Cd 20 [68], 1346 K for SmPdGa 3 [69], 1366 K for HP-SmPdSn [70], but also even higher values such as ΔE = 2691 K for SmPt 6 Al 3 are known [71]. (Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 95%
“…Measurements of the magnetic properties of these materials revealed that only Gd 3 Pt 4 Ge 6 and Tb 3 Pt 4 Ge 6 were antiferromagnetically ordered while others were paramagnetic. 20 A pure phase of polycrystalline Dy 3 Pt 4 Ge 6 could not be synthesized, and thus its magnetic properties were not reported. 20 Here, we replaced Ge with Sb and obtained millimeter-sized single crystals of Dy 3.00(1) Pt 2 Sb 4.48 (2) with crystallographic disorder on both Dy and Sb sites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 A pure phase of polycrystalline Dy 3 Pt 4 Ge 6 could not be synthesized, and thus its magnetic properties were not reported. 20 Here, we replaced Ge with Sb and obtained millimeter-sized single crystals of Dy 3.00(1) Pt 2 Sb 4.48 (2) with crystallographic disorder on both Dy and Sb sites. Dy 3.00(1) Pt 2 Sb 4.48 (2) appears to be a new material which crystallizes in a structural type similar to that of RE 3 Pt 4 Ge 6 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation